2011
DOI: 10.19090/pp.2011.3.229-244
|View full text |Cite
|
Sign up to set email alerts
|

Faktori rizika za pojavu vršnjačkog nasilja u osnovnim školama

Abstract: RezimeVršnjačko nasilje je veoma aktuelan problem u našim školama. Cilj ovog istaživanja je da utvrdi koji prediktori -faktori rizika iz domena vaspitanja i uslova odrastanja i u kojoj meri doprinose nastanku i ispoljavanju vrš-njačkog nasilja u osnovnim školama. Ukupan uzorak činilo je 504 ispitanika, učenika osnovnih škola od trećeg do osmog razreda. U istraživanju su korišćeni sledeći instrumenti: Upitnik vaspitnih stavova, Upitnik za merenje pojavnih oblika i učestalosti vršnjačkog nasilja i Upitnik za uči… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
2
3
0
4
Order By: Relevance
“…Also, obtained results in some other studies suggested that two different types of abuse, psychological and physical, were highly correlated (Baldry, 2003) and that frequency of verbal disagreements and high levels of interpersonal conflict are strongly associated with physical violence (Hoffman et al, 1994;Jewkes et al, 2002). Furthermore, some authors found that psychological type of violence can precede or follow or co-occur with physical type of violence (Lukić & Jovanović, 2003;Nedimović & Biro, 2011;Stets, 1991). It showed that most women who experience physical violence by their intimate partner also report that they experience psychological violence (Dutton & Painter, 1993).…”
Section: Physical and Psychological Violencementioning
confidence: 92%
“…Also, obtained results in some other studies suggested that two different types of abuse, psychological and physical, were highly correlated (Baldry, 2003) and that frequency of verbal disagreements and high levels of interpersonal conflict are strongly associated with physical violence (Hoffman et al, 1994;Jewkes et al, 2002). Furthermore, some authors found that psychological type of violence can precede or follow or co-occur with physical type of violence (Lukić & Jovanović, 2003;Nedimović & Biro, 2011;Stets, 1991). It showed that most women who experience physical violence by their intimate partner also report that they experience psychological violence (Dutton & Painter, 1993).…”
Section: Physical and Psychological Violencementioning
confidence: 92%
“…Nasilje se odvija u narušenoj komunikaciji i interakciji nasilnika i žrtve, a kada je riječ o nasilju u obitelj,i nasilnik i žrtva su u međusobnoj formalnoj, kulturološkoj, socijalnoj i emocionalnoj povezanosti (Mamula i sur., 2013). Etiologija nasilja je složena, a među rizične faktore ubrajaju se obiteljski i genetski faktori, poremećaji ličnosti, socio-ekonomski status, poremećena socijalna kognicija i sustav vrijednosti, ovisnosti te širi kulturološki i socijalni faktori (Nedimović i Biro, 2011). Teorijska objašnjenja nasilja uključuju različite faktore poput: genetike i bioloških faktora, socijalnog učenja, reakcije na frustraciju i psihopatologije, a uključuju osobine i nasilnika i žrtve.…”
Section: Nasilje U Obitelji I Partnerskim Vezamaunclassified
“…To potvrđuje i Bandurina teorija socijalnog učenja: socijalno-kognitivna teorija (Popadić, 2009). U istraživanju Canadian Longitudinal Survey of Children and Youth, rezultati pokazuju da deca koja prisustvuju nasilju u kući, češće na direktan ili indirektan način zlostavljaju svoje vršnjake (Nedimović & Biro, 2011). Četvrti faktor rizika, prema Olveusovom mišljenju, jeste temperament deteta (Batić, 2013).…”
Section: Sociološki Aspekt Elektronskog Nasiljaunclassified